2006
DOI: 10.1093/humrep/del025
|View full text |Cite
|
Sign up to set email alerts
|

The use of metformin for women with PCOS undergoing IVF treatment

Abstract: Short-term co-treatment with metformin for patients with PCOS undergoing IVF/ICSI cycles does not improve the response to stimulation but significantly improves the pregnancy outcome and reduces the risk of OHSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
4
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(160 citation statements)
references
References 64 publications
8
138
4
7
Order By: Relevance
“…Some authors have suggested that the concomitant use of metformin while patients are being stimulated for IVF not only might increase the pregnancy rates but also could decrease the incidence of OHSS. 38 Conversely, a recent meta-analysis by Costello et al 39 did not demonstrate any benefits from the cotreatment with metformin.…”
Section: Anovulationmentioning
confidence: 95%
“…Some authors have suggested that the concomitant use of metformin while patients are being stimulated for IVF not only might increase the pregnancy rates but also could decrease the incidence of OHSS. 38 Conversely, a recent meta-analysis by Costello et al 39 did not demonstrate any benefits from the cotreatment with metformin.…”
Section: Anovulationmentioning
confidence: 95%
“…Metformin is a biguanide who mainly acts by reducing hepatic glucose production, but also improves insulin sensitivity to some extent. This drug also reduces appetite in many PCOS women and is thus often [133], but not always [134], associated with more weight loss. Metformin has been shown to be effective in all women with PCOS, even those without insulin resistance and hyperinsulinemia [47, [135][136][137], but tends to be more effective in lean as compared to obese PCOS women [138].…”
Section: Insulin-sensitizing Drugsmentioning
confidence: 99%
“…The Norwegian group 32 observed that the lean sub-group showed a statistically increased pregnancy rate, and the study by Tang et al, 33 which included relatively lean patients in the whole study group, showed an unambiguous improvement in pregnancy rate. A large multi-centre study is now addressing this issue and we await the outcome with some anticipation It would appear that the mechanism for any beneficial effect is unrelated to changes in FSH sensitivity and gross ovarian responses, as these were not influenced by metformin treatment in either study.…”
Section: Metformin In Assisted Conception (Ivf/icsi)mentioning
confidence: 96%
“…The main observations in two randomised control studies 32,33 indicate that relatively short-term metformin treatment does not influence total follicular responses to exogenous FSH, evidenced by numbers of follicles, duration and dose of FSH and numbers of oocytes. This is an important observation, leading us to conclude that short-term modulation of the insulin and androgen environment does not affect either the stockpile of follicles awaiting FSH stimulation or the sensitivity of those individual follicles to FSH stimulation in terms of growth rate and amount of FSH required to achieve maturation.…”
Section: Metformin In Assisted Conception (Ivf/icsi)mentioning
confidence: 99%